Development of a Tourism Village Efforts to Empower the Community's Economy from an Islamic Economic Perspective: A Case Study of West Lombok's Kebon Ayu - Kurniati Fitri, Zahratul Aini; Mansyur, Zainudin; Mulhimmah, Baiq Ratna (Universitas Alma Ata, 2023)
The tourism sector in the world economy has a role to play as a contributor to employment and economic growth. In the current era of regional autonomy, villages are given the authority to regulate wider community interests, aiming to accelerate the realization of community welfare through service, empowerment, and the role of village communities, as well as increasing regional competitiveness by taking into account the principles of equity and justice. The development of tourism villages is a new idea related to the utilization of village potential, which is expected to be packaged into tourism products that can preserve local wisdom, where community empowerment becomes a public concern and is considered one of the appropriate approaches in overcoming the problem of poverty. So that empowerment can form an economically self-sufficient society. This study aims to find out how to implement the economic empowerment of the people of Kebon Ayu Village through the Tourism Village Program and what obstacles are encountered in this implementation. The research method used is qualitative research with data collection carried out using observation, documentation, and interviews. Data analysis techniques are carried out by reducing, presenting, and drawing conclusions. The results of the study show that community economic empowerment through the Tourism Village program has a positive impact on increasing people's income and creating employment opportunities through training and providing business facilities. The main obstacles faced were the lack of business capital, lack of public awareness, and inadequate promotion and marketing media.